Efektivitas Pembelajaran Online Pada Pendidikan Tinggi Kesehatan Di Masa Pandemi Covid-19 - I Made Sundayana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The condition of the COVID-19 pandemic that has entered the world, new changes in refuge in various sectors including education, especially health. The educational process must continue to run conducive without reducing and eliminating learning objectives. This type of research is a cross-sectional quantitative study with a survey approach. The research instruments were questionnaires and interview sheets given to student nurses, midwives and pharmacies at STIKes Buleleng. Quantitative data analysis used univariate analysis and chi square. The results show that the results show that the majority of respondents come from 71.05% of the nursing study program, use a hotspot / mobile quota 84.87%, do not see the purpose of the course 88.08%, the proportion of material understanding is 50% of 44.74%, it is necessary video for each learning is 84.21%, and online learning is not as effective as 51.32%. Online effectiveness is related to course objectives, and the proportion of understanding of the material provided.